Perspectives on TB patients' care and support: a qualitative study conducted in Accra Metropolis, Ghana - Faustina Twumwaa Gyimah; Phyllis Dako-Gyeke (BMC, 2019)
Abstract Background Tuberculosis (TB) was declared a global emergency in 1993 by the World Health Organization (WHO). Despite available interventions initiated by the WHO and some countries, the disease remains a key public health problem. The rates of TB infection and its associated burden is unevenly distributed across the globe with greater severity in low-to-middle income countries. This paper therefore explored the experiences of TB patients and health care providers pertaining to patients' care and support during treatment, in the Accra Metropolis of Ghana. Methods A qualitative approach using phenomenology was employed to explore participants' experiences. Maximum variation sampling, a type of purposive sampling was employed in selecting participants who exhibit a wide range of behaviours and experiences. Thirty (30) In-depth Interviews and three (3) Key Informant Interviews were conducted in selected facilities within a period of three months in 2018. The data was audio-recorded, transcribed, and transported into Nvivo version 11, for data management and coding. Content analysis of data was carried out for the generation of themes. Results The findings revealed that good knowledge of TB treatment practices did not spontaneously shape perceptions towards treatment. Factors including prevailing cultural beliefs, physical and psychological stress, consequences of patient's interrupted labour and health system challenges were hindrances in caring for TB patients. Physical, mental and spiritual mechanisms were adopted to cope with challenges. Conclusion Personal patient-related challenges and health system bottlenecks were major influencing factors in providing care and support to TB clients. The National Tuberculosis control Program (NTP) of Ghana should adopt measures and provide the required financial, infrastructural and human resources for the augmentation of patients' treatment.